PENGEMBANGAN MEDIA SMART BOX PADA MATERI PENERAPAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI DI KELAS V SEKOLAH DASAR - Saluni, Mila; Pomalingo, Samsi; Ismail, Reska Putri (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to develop Smart Box learning media that meets the criteria of feasibility, practicality, and effectiveness in Civics learning to improve student learning outcomes in the material on the Application of Pancasila Values ​​in Daily Life. This study uses the (Research and Development) method using the ADDIE development research model, which includes the stages of analyze, design, development, Implement, and Evaluate. The feasibility of the Smart Box media was tested through validation by a team of experts. The results of the media validation obtained a score of 95, including the "Very Good" category and obtained a percentage of 95% so that it falls into the "Very feasible" criteria. Material validation obtained a total score of 34, including the "Very Good" category and obtained a percentage of 85% so that it falls into the "Very feasible" criteria. To test practicality, the researcher used a teacher observation sheet, which showed a total score of 40 out of a maximum score of 40, with an average practicality percentage reaching 100%, falling into the very practical category. This media obtained an average percentage of 93.33%, which is categorized as very suitable for use by teachers and students in elementary schools. In terms of effectiveness, the application of media in class V SDN No. 62 Kota Timur was measured through pretest and posttest. As a result, the total pretest score of 37.05 increased to 86.47 in the posttest, with an increase of 49.42%. The N-Gain calculation showed a score of 0.77, which is included in the "moderate" category. Based on these results, the Smart Box media has been proven to improve student learning outcomes and is very effective for use in learning in elementary schools